Nilai- Nilai Pendidikan Dalam Surat Al-An’am Ayat 162 Tentang Kompetensi Kepribadian Guru Kajian Ilmu Pendidikan Islam - Izzan, Ahmad; Fitriana, Dyna Nur (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
This study is motivated by educational challenges related to the role of teachers. Teachers play a pivotal role in the educational process, and their personalities significantly contribute to the success of education. The Qur'an, as the highest source of guidance in education, contains numerous verses that address the competencies and characteristics of a teacher's personality. One such reference is found in Surah Al-An'am, verse 162, which highlights the importance of sincerity in teaching. The objective of this research is to describe the educational values contained in Surah Al-An'am, verse 162, concerning the personality competencies of teachers from the perspective of Islamic Educational Sciences. This research is a type of library research, involving the examination of interpretations by various Islamic scholars (mufassir) on Surah Al-An'am, verse 162, as well as written sources on educational values proposed by experts and Islamic scholars. The methodology employed in this research is descriptive, focusing on content analysis of Surah Al-An'am, verse 162, and relevant textual materials. The data analysis technique used is thematic interpretation (tafsir). The findings indicate that the educational values derived from Surah Al-An'am, verse 162, as interpreted by scholars, emphasize the importance of sincerity. The educational values in this verse regarding the personality competencies of teachers within the study of Islamic Educational Sciences include:   I'tiqodiyah Values (Faith) - Emphasizing the necessity of sincere belief and faith in a teacher's life. Shari'ah Values - Highlighting the importance of sincere adherence to Islamic law and religious practices. Khuluqiyah Values (Morality) - Stressing the need for sincere conduct and behavior in all interactions.   These values underscore the fundamental requirement for a teacher to embody sincerity in their faith, worship, and behavior. Such values form the foundation for nurturing a spirit that aligns with the broader societal expectations and aspirations for education.  Keywords: Educational Values, Teacher's Personality Competence, Islamic Educational Sciences